Safety, Tolerability, and Pharmacokinetic Characteristics of a Novel Nonopioid Analgesic, VVZ‐149 Injections in Healthy Volunteers: A First‐in‐Class, First‐in‐Human Study. (16th August 2017) - Oh, Jaeseong; Lee, SeungHwan; Kim, Anhye; Yoon, Jangsoo; Jang, Kyungho; Lee, Doo H.; Cho, Sunyoung; Lee, Sang Rim; Yu, Kyung‐Sang; Chung, Jae‐Yong
Abstract: VVZ‐149, a dual antagonist of GlyT2 and 5HT2 A receptors, is an investigational analgesic with a novel mechanism of action that is currently under early‐stage clinical development as an injectable agent for the treatment of postoperative pain. Here, the safety, tolerability, and pharmacokinetics of VVZ‐149 injections in healthy male volunteers were explored in a randomized, double‐blind, single‐ and multiple‐ascending‐dose (SAD and MAD, respectively), placebo‐controlled clinical study. Subjects randomly received a 4‐hour intravenous infusion of 0.25‐8 mg/kg VVZ‐149 or placebo in the SAD study (n = 46) or a 4‐hour intravenous infusion of 4–7 mg/kg VVZ‐149 or placebo twice daily for 3 days in the MAD study (n = 20). Serial blood and urine samples were collected for the pharmacokinetic analysis of VVZ‐149 and its active metabolite (VVZ‐368). Noncompartmental and compartmental pharmacokinetic analyses were performed. Various dosing scenarios were simulated to identify the adequate dosing regimen for the subsequent trials. Plasma exposure to VVZ‐149 and VVZ‐368 showed a dose‐proportional increase. VVZ‐149 did not accumulate in the plasma, whereas the plasma concentration of VVZ‐368 increased by 1.23‐ to 2.49‐fold after the fifth and sixth doses, respectively, in the MAD trial. Among the simulated dosing regimens, a loading dose followed by a maintenance dose was found to be an optimal dosing regimen, yielding the effective concentration estimated from animal studies in rat models of neuropathic or inflammatory pain. Single‐ or multiple‐dose administration of VVZ‐149 was generally well tolerated. These results showed that 0.5–8 mg/kg VVZ‐149 exhibited linear pharmacokinetic characteristics and can be safely administered in further clinical studies.